THE THERAPEUTIC IMPACT OF PROBIOTICS ON NONALCOHOLIC FATTY LIVER DISEASE IN PEDIATRICS: A SYSTEMATIC REVIEW - Felipe Galvão Batista Chaves; Glauco Ferreira de Oliveira; João Paulo Ribeiro; João Victor Serafim; Luiz Felipe Medeiros Cordeiro; Matheus Alves Alvares; Marcelo Trindade Cecchi; Murilo Cordeiro Vasquez; Thaísy Bianka Dorta de Souza; Vera Esteves Vagnozzi Rullo (Revista Paulista de Pediatria, 2020)
ABSTRACT Objective: Evaluate the effects of probiotics use, compared with placebo, in pediatric patients with non-alcoholic fatty liver disease (NAFLD), using laboratorial and ultrasonographic parameters as outcomes. Methods: A systematic review of the literature was performed through MEDLINE and Lilacs databases. The articles selected were randomized controlled clinical trials published until November 2018, without any language restriction, dealing with pediatric patients with NAFLD. Patients were divided into 2 groups. One group received probiotic therapy and the other group, only received placebo. The primary outcome evaluated was the difference between the serum levels of alanine aminotransferase (ALT) before and after receiving probiotics or placebo. The secondary outcomes evaluated were the serum aspartate aminotransferase levels, body mass index, serum triglycerides, waist circumference and level of liver steatosis on the ultrasonography. Results: A total of 46 articles were recovered, and 3 articles were included in the qualitative analysis, totaling 128 patients. Two trials revealed a significant decrease of alanine aminotransferase levels after treatment with probiotics (Lactobacillus rhamnosus for 8 weeks; Bifidobacterium+Lactobacillus for 12 weeks), when compared to the placebo. The other variables did not show a statistically significant difference between both groups. Conclusions: Probiotic therapy has contributed to the reduction of ALT serum levels in pediatric patients with nonalcoholic fatty liver disease, which is in line with results found by other authors in scientific literature. Regarding the secondary outcomes, the use of probiotics did not show benefits or damages compared to placebo.